On ‘False, Collusive Objectification’: Becoming Attuned to Self-Censorship, Performance and Interviewer Biases in Qualitative Interviewing - Yanos, Philip T. (2008)
In this paper, we discuss a problem in qualitative interviewing labeled by Bourdieu as ‘false, collusive objectification’. As described by Bourdieu, interviews where this occurs appear authentic because they often echo social science concepts and terminology and therefore may please the interviewer; however, they are actually unusable. We evaluate Bourdieu’s claim for the existence of ‘false’ interviews in light of the predominant postmodern position in qualitative research, offer examples from our own research on people diagnosed with mental illness and raise the issue of whether, when and how qualitative researchers should concern themselves with the shortcomings of interviews. We conclude with suggestions derived from Bourdieu’s view on how to address the problem he described.